Tailoring the structural, morphological, optical, thermal and dielectric characteristics of ZnO nanoparticles using starch as a capping agent - Sagadevan, Suresh; Vennila, Selvaraj; Lett, Jayasingh Anita; Marlinda, Ab Rahman; Hamizi, Nor Aliya; Johan, Mohd Rafie (Elsevier, 2019)
Using Starch as a capping agent, zinc oxide (ZnO) nanoparticles (NPs) have been synthesized by the low cost and simple chemical precipitation technique. The confirmation of the hexagonal crystal structure of ZnO NPs were demonstrated by X-ray powder diffraction (XRD) pattern. The Fourier-transform infrared spectroscopy (FTIR) spectroscopy confirms Zn-O stretching vibrations. The scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) images reveal the surface morphological properties of ZnO NPs. Optical properties were investigated by UV–Visible spectroscopy. The optical characterization shows that the ZnO NPs exhibits a low absorbance in the visible range. Thermal behavior of ZnO NPs studied using thermogravimetric analysis (TGA) and differential thermal analysis (DTA). Dielectric properties of ZnO NPs are analysed in the different frequencies at different temperatures. The dielectric properties of ZnO NPs were attributed to the interfacial polarization at low frequencies and orientational polarization at higher frequencies. Therefore, the synthesis method has potential for application in manufacturing units due to ease processing and more economical reagents. © 2019 The Authors